Milk in the Qur’an: Hamka’s Interpretation of Surah An-Nahl Verse 66 in Tafsir Al-Azhar - Wahyu Apriandi Batubara; Syahrin Harahap (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study analyzes the concept of milk in the Qur’an through Hamka’s interpretation in Tafsir Al-Azhar, with particular emphasis on Surah An-Nahl verse 66. It employs qualitative library research and combines thematic exegesis with scientific exegesis. The primary data are drawn from Hamka’s commentary on Surah An-Nahl verse 66 and related Qur’anic passages, while the secondary data comprise exegetical works, hadith collections, and literature on animal biology and modern nutrition. The data were analyzed through close reading, thematic classification, interpretive reconstruction, and comparison with established scientific accounts. The findings show that Hamka understands milk as an ‘ibrah that reveals Allah’s creative power and wisdom through an ordered biological process. The phrase labanan khalisan emphasizes that milk emerges as a pure and palatable substance despite its physiological relationship with digested matter and blood. Contemporary biology clarifies this process through digestion, nutrient absorption, blood circulation, hormonal regulation, and mammary-gland activity. Nutritional research further identifies milk as a source of protein, calcium, phosphorus, fats, vitamins, and minerals that support growth and health. These scientific explanations clarify the natural phenomenon referenced by the verse without replacing its theological and ethical purposes. The study contributes a three-layered framework that integrates the theological, biological, and health-related meanings of milk in the Qur’an.